A Comparison of four Methods to Evaluate the Butterfly Abundance. Using a Tropical Community - Monge Nájera, Julián (1991)
In recent years. several transect methods to evaluate the abundance of butterflies have been proposed (Pollard, E. 1977, Biol. Conserv. 12:115—134; Feltwell, 3. 1982. Proc. Trans. Br. Entomol. Nat. Hist. Soc. 15:17—24). but to our knowledge there has been no attempt to compare experimentally their usefulness in relation to the availability of time and resources. Herein, we present the results of an experiment in which modifications of four of those methods were applied, simultaneously, to a community of neotropical butterflies